A new enantioselective dioxygenase for the (S)-enantiomer of the chiral herbicide dichlorprop in Sphingopyxis sp. DBS4. (January 2023) - Zhang, Long; Song, Man; Mao, Zhenbo; Liu, Yuan; Li, Feng; Jiang, Jiandong; Chen, Kai
Abstract: Dichlorprop [( R, S )-2-(2, 4-dichlorophenoxy)propanoic acid], a chiral herbicide belonging to phenoxyalkanoic acid herbicides, is extensively used around the world, and is frequently detected in various habitats. Although ( S )-dichlorprop has no herbicidal activity, its toxicity and ecological risk are higher than ( R )-dichlorprop. In our previous studies, the isolated strain Sphingopyxis sp. DBS4 was confirmed to mineralize both ( R )-dichlorprop and ( S )-dichlorprop, but the key genes responsible for the initial degradation of ( R )-/( S )-dichlorprop were still unclear. Here, based on genome sequencing and enzyme purification, a new dioxygenase gene, spoA, responsible for the initial transformation of ( S )-dichlorprop to 2, 4-dichlorophenol and pyruvate was cloned from the rac -dichlorprop-utilizing strain of Sphingopyxis sp. DBS4. SpoA, an α -ketoglutarate-dependent dioxygenase, exhibited low amino acid sequence identity to the reported ( S )-dichlorprop-transforming dioxygenase SdpA (34.8%), and showed enantioselective activity toward ( S )-enantiomers of dichlorprop and mecoprop, but no activity toward the corresponding ( R )-enantiomers. The K m value of SpoA for ( S )-dichlorprop was 134.3 μM, and the k cat / K m was determined to be 7.5 × 10 −2 μM −1 s −1 . Molecular docking and site-directed mutagenesis showed that two residues of SdpA, Lys101 and Asp119, are the key sites for the enantioselective transformation of ( S )-dichlorprop. Our study identifies a new dioxygenase for the enantioselective transformation of ( S )-dichlorprop and deepens our understanding of the microbial catabolism of chiral phenoxyalkanoic acid herbicides. Highlights: SpoA catalyzes the enantioselective transformation of ( S )-dichlorprop. SpoA exhibits low sequence identity to the reported dioxygenases RdpA and SdpA. Lys101/Asp119 of SdpA play important roles in the transformation of ( S )-dichlorprop.